Prefácio - Rodrigues, Nathalia Kosinski; Ceretta, Bruno José Queiroz; José, Diego Flávio Fontoura; Risso, Estéfano Elias; Gonçalves, Frederico Paganin; Sliwka, Gregório Schroder; Almeida, Lúcio Antônio Machado; Souza, Maria Gabriela Borges Puente de; Petiz, Martin Magnus; Pilatti, Nathália de Campos; Kretzmann, Renata Pozzi; Flores, Alfredo de Jesus Dal Molin (Revista da Faculdade de Direito da UFRGS, 2021)
Prefácio ao n. 47 da Revista da Faculdade de Direito da UFRGS.